2016
DOI: 10.1063/1.4944456
|View full text |Cite
|
Sign up to set email alerts
|

A multiplexed immunoaggregation biomarker assay using a two-stage micro resistive pulse sensor

Abstract: We present an immunoaggregation assay chip for multiplexed biomarkers detection. This chip is based on immunoaggregation of antibody functionalized microparticles (Ab-MPs) to quantify concentrations of multiple biomarkers simultaneously. A mixture of multiple types of Ab-MPs probes with different sizes and magnetic properties, which were functionalized by different antibodies, was used for the multiplexed assay. The interactions between biomarkers and their specific Ab-MPs probes caused the immunoaggregation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Therefore, the competitive immuno-aggregation method presented in this paper has three major advantages: 1) this method has a lower detection limit (0.01 ng/mL) than the method in our previous work. 57,58 This is because our previous study used non-competitive molecular binding between recognition biomolecules and target proteins. Non-competitive binding usually requires a large amount of target proteins to initiate the formation of MP aggregates, which could compromise the sensitivity of the assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the competitive immuno-aggregation method presented in this paper has three major advantages: 1) this method has a lower detection limit (0.01 ng/mL) than the method in our previous work. 57,58 This is because our previous study used non-competitive molecular binding between recognition biomolecules and target proteins. Non-competitive binding usually requires a large amount of target proteins to initiate the formation of MP aggregates, which could compromise the sensitivity of the assay.…”
Section: Discussionmentioning
confidence: 99%
“…The equilibrium dissociation constant of the binding between VEGF and VEGF Ab was reported to be 9.94 pM 56 The commercial VEGF Abs have comparable binding affinities; 2) the high binding capacity of the MPs because of their large surface-to-volume ratio. Additionally, in contrast to the non-competing aggregation method, 57,58 this assay generated a monotonic standard curve without any saturation effect; i.e., when the target protein saturated and blocked the surface of the MPs, fewer aggregates can be formed with the blocked microparticles. 57,58 Thus, for the competitive immuno-aggregation method, the corresponding VEGF concentration and the average volume change of aggregates/particles forms an injective relation.…”
Section: Validation Of Microfluidic Immuno-aggregation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently microparticle based immuno-aggregation methods [107][108][109][110][111][112] have been developed to (1) amplify the size change caused by specific binding and (2) enable multiplexed detections of multiple biomarkers. Han et al have used microparticles with different sizes and magnetic property as platforms for immuno-aggregation.…”
Section: Particle Based Multiplexingmentioning
confidence: 99%
“…Han et al have used microparticles with different sizes and magnetic property as platforms for immuno-aggregation. 112 The method can quantify concentrations of multiple biomarkers simultaneously based on measuring the immuno-aggregates of antibody functionalized microparticles (Ab-MPs). Further Han et al developed a two-stage micro Coulter counter [as shown in Fig.…”
Section: Particle Based Multiplexingmentioning
confidence: 99%